Unveiling one of the rarest 'butterflies' ever (Lepidoptera: Hesperiidae, Noctuidae). (3rd November 2018) - Zilli, Alberto; Grishin, Nick V.
Abstract: Many insect species named by the Danish entomologist J.C. Fabricius remain enigmatic due to loss of the original type specimens, sketchy descriptions and lack of illustrations, but even some well‐illustrated taxa remain unrecognized. This is the case for Hesperia busiris, a 'butterfly' illustrated by W.J. Jones, the identity of which has puzzled experts for 225 years. Here we argue that the description and illustrations of this species are a perfect fit to a colourful moth later described by F. Walker as Eusemia contigua . Furthermore, we present evidence that Walker unwittingly based his name on the same specimen as Fabricius, and that this is the only known example of this species. An extraordinary sequence of misconceptions led the geographic origin of this specimen to become thoroughly confused, so that it is currently unknown where on Earth this species may occur (although a substantial body of evidence points to West Africa) and if it is even still extant. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:3D148142‐C738‐4368‐9CA8‐69789A6D3E6A . Abstract : Fabricius described in 1793 a 'butterfly', Hesperia busiris, of which only paintings done by Jones around 1787 exist. Alternatively considered to be an Asiatic or an American member of family Hesperiidae, we discovered that it corresponds to Heraclia contigua, an agaristine noctuid moth known only after one specimen. Ownership history and features of this specimen show that it is the same as the original of H. busiris and that this species is most likely West African, and is possibly extinct.